Estetika Film Animasi 2D â€œ Bawang dan Kesunaâ€ - Sudi Anggara, I Gede Adi; Mudra, I Wayan; Sariada, I Ketut (PANTUN, 2018)
2D Animation flm of Bali folktale â€œBawang and Kesunaâ€ tells about two sisters, Bawang and Kesuna. Bawang is a girl who is lazy, jealousy, and sly. Meanwhile, Kesuna is a kind, calm, honest, and hardworking girl. The folktale is from Sengkidu village, Karangasem. The paper is aimed to reveal the aesthetics of 2D â€œBawang and Kesunaâ€ flm approached by Djelantik Aesthetic theory. It discusses the form and structure, the mood, idea and message, as well as the presentation. The study applies qualitative method. The data are collected from interview and documentation of related literatures. The result shows that the form comprises illustration, typography, and colour, meanwhile the structure applies flm structure, namely shot, scene, and sequence. The mood shares village atmosphere giving traditional impression shown from the accessories of costumes and buildings. The film is full of moral messages useful for children character education.Keywords: Aesthetics, 2D Animation Film, Balinese Folktale, Bawang and Kesuna